Taboo Words in End of Watch Movie - Simamora, Mikhael Manahan; Tangkas, I Wayan Dirgeyasa (Universitas Negeri Medan, 2022)
This research attempts to find out the types of the taboo words expressed by characters in End of Watch Movie by identifying it and to explain the motives for taboo words expressed by the characters in the End of Watch Movie. This research utilized a theory from Jay (1992). This research utilized a design of a descriptive method which is a method for research that endeavors to depict and interpret the articles as per reality. The data of this research are in the linguistic features found in the movie. The data are quantities of English taboo words that contain transcripts in the movie. The data in this research were collected by using documentary techniques. In order to collect data, recorder technique is used as the instrument to collect the data. The technique of analyzing data will be examined by utilizing descriptive qualitative methods. The results of the research show that there are 113 data and for the taboo words type of scatology is the frequently used by the characters with the rate 23,89% and the most motive used is anger and frustration with the rate 30,09%.